1-(3-Pyridyl)pyrrolidine-2,5-dione - Luan-Fang Yang (Acta Crystallographica Section E, 2009)
In the title molecule, C9H8N2O2, the dihedral angle between the pyridine and the pyrrolidine rings is 64.58 (12)°. In the crystal structure, weak C—H...π-electron ring interactions stabilize the packing.